Diversity, migration routes, and worldwide population genetic structure of Lecanosticta acicola, the causal agent of brown spot needle blight. (11th August 2022) - Laas, Marili; Adamson, Kalev; Barnes, Irene; Janoušek, Josef; Mullett, Martin S.; Adamčíková, Katarína; Akiba, Mitsuteru; Beenken, Ludwig; Braganca, Helena; Bulgakov, Timur S.; Capretti, Paolo; Cech, Thomas; et al.
Abstract: Lecanosticta acicola is a pine needle pathogen causing brown spot needle blight that results in premature needle shedding with considerable damage described in North America, Europe, and Asia. Microsatellite and mating type markers were used to study the population genetics, migration history, and reproduction mode of the pathogen, based on a collection of 650 isolates from 27 countries and 26 hosts across the range of L. acicola . The presence of L. acicola in Georgia was confirmed in this study. Migration analyses indicate there have been several introduction events from North America into Europe. However, some of the source populations still appear to remain unknown. The populations in Croatia and western Asia appear to originate from genetically similar populations in North America. Intercontinental movement of the pathogen was reflected in an identical haplotype occurring on two continents, in North America (Canada) and Europe (Germany). Several shared haplotypes between European populations further suggests more local pathogen movement between countries. Moreover, migration analyses indicate that the populations in northern Europe originate from more established populations in central Europe. Overall, the highest genetic diversity was observed in south‐eastern USA. In Europe, the highest diversity was observed in France, where the presence of both known pathogen lineages was recorded. Less than half of the observed populations contained mating types in equal proportions. Although there is evidence of some sexual reproduction taking place, the pathogen spreads predominantly asexually and through anthropogenic activity. Abstract : The pine needle pathogen Lecanosticta acicola has been introduced into Europe on several separate occasions with human activity supporting the pathogen's onwards spread from already established European populations into new areas.